Culinary Spices in Food and Medicine: An Overview of Syzygium aromaticum (L.) Merr. and L. M. Perry [Myrtaceae] - Otunola, Gloria Aderonke (Frontiers in Pharmacology, 2022)
Spices- dried aromatic parts of plants (leaves, seeds, bark, roots, rhizomes, buds, etc,) used to enhance flavour, taste and colour (sensory quality) of foods, are increasingly finding other useful roles in healthcare beyond their primary use as culinary organoleptic enhancers. Several spices are currently being investigated for their potential health benefits, because of the failing efficacy, toxicity and high cost associated with conventional drugs. One such spice: Syzygium aromaticum (L.) Merr. & L.M.Perry [Myrtaceae] (Clove), has a multi-dimensional role in diet, medicine, functional foods and nutraceuticals, agriculture, among other industries. Peer-reviewed articles, mostly from PubMed and Google Scholar, were consulted for the purpose of this review. The nutritional and phytochemical contents, selected biological activities as well as some functional foods and beverages of clove and their uses for human health are presented. Although these observations are largely empirical, the efficacious attributes have led to their pharmacological applications in the indigenous system of medicine all over the world and bridge between food, diet and medicine. Considering the GRAS status of clove, more studies on bioavailability, accumulation, toxicity, dosage and efficacy of clove as a spice drug or functional foods in biological systems especially in humans are required. Meanwhile, clove and its products can be used as co-adjuvants in the prevention, treatment and management of chronic diseases. Further, many applications of clove in food, health, cosmetics, pharmaceutics, nanoparticles and agricultural industries are still open for investigations.